Interactive Multimedia Development in Learning of Film Review Text for 8th Grade Students in Senior High School (SMP) 1 Tanjungmorawa - Eva Lindasari; Khairil Ansari; Marice Marice (BIRCU, 2019)
This study aims to produce interactive multimedia development in learning of film review text for 8th grade students in Senior High School (SMP) 1 Tanjungmorawa. The research method uses Research and Development method which refers to the development of the Borg and Gall which was modified by Sugiyono. The results of the validation of material experts on the feasibility of the content obtained an average of 90.7% in the category of